Pengaruh Pendapatan Rata-Rata Terhadap Tingkat Konsumsi di Sumatera Utara - Karolin Gabrela Sitanggang; Nadia Natalia Sinurat; Ninda Rohani Situmorang; Rahel Marito Tambunan; Rexsy Mardohot Sitanggang; Nicko Fernando Rajagukguk; Dian Maulina Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Income plays a very important role in determining individual consumption patterns, reflecting consumers' purchasing power towards goods and services. This study investigated the impact of average income on consumption levels in North Sumatra, focusing on the relationship between income and shopping behavior in the region. The purpose of this study was to study how variations in average income affected consumer spending habits and general economic activity in North Sumatra from 2020 to 2022. This study used secondary data from the Central Bureau of Statistics (BPS) North Sumatra, which included per capita consumption levels and average income. The data were analyzed using multiple linear regression method. The results showed a positive and significant relationship between average income and consumption levels in North Sumatra in 2020–2022; In other words, the higher the average income, the greater the per capita consumption. The research highlights the importance of stability and income growth in stimulating consumer spending, thereby boosting economic growth.